Does the APACHE II score predict performance of activities of daily living in patients discharged from a weaning center? - Rojek-Jarmuła, Anna; Hombach, Rainer; Krzych, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: Data regarding the functional status of patients after prolonged mechanical ventilation are scarce, and little is known about its clinical predictors. Aim: To investigate whether the Acute Physiology and Chronic Health Evaluation (APACHE) II score on admission may predict performance in activities of daily living on discharge from a weaning center. Material and methods: All consecutive patients admitted between January 1, 2012 and December 31, 2013 were enrolled (n = 130). During this period, 15 subjects died, and 115 were successfully discharged (34 women; 81 men). APACHE II was calculated based on the worst values taken during the first 24 hours after admission. On discharge, the Barthel Index (BI) and its extended version, the Early Rehabilitation Barthel Index (ERBI), were assessed. Results: Median BI was 20 points (IQR 5; 40), and ERBI was 20 points (–50; 40). There was no correlation between APACHE II and either BI (R = –0.07; p = 0.47) or ERBI (R = –0.07; p = 0.44). APACHE II predicted the need for assistance with bathing (AUROC = 0.833; p < 0.001), grooming (AUROC = 0.823; p < 0.001), toilet use (AUROC = 0.887; p < 0.001), and urination (AUROC = 0.658; p = 0.04). APACHE II had no impact on any ERBI items associated with ventilator weaning, including the need of further mechanical ventilation (AUROC = 0.534; p = 0.65) or tracheostomy (AUROC = 0.544; p = 0.42). Conclusions: Although APACHE II cannot predict the overall functional status in patients discharged from a weaning center, it helps identify subjects who will need support with bathing, grooming, and toilet use. The APACHE II score is inadequate to predict performance in activities associated with further respiratory support.